PENYULUHAN JUMAMPAH (JURU PEMANTAU SAMPAH) TERHADAP PENGETAHUAN DAN PRAKTIK TENTANG MEMILAH DAN MENABUNG SAMPAH DI SEKOLAH DASAR KECAMATAN MERGANGSAN - Reza Monica Putri; Naris Dyah Prasetyawati; Bambang Suwerda (Sekolah Tinggi Pariwisata Mataram, 2020)
Current waste management problems often occur in Yogyakarta. This is due to population growth which results in an increase the amount of waste generated. The occurrence is certainly not comparable with the area and number of Final Disposal Sites that do not increase. One method of waste management that can be applied is a Waste Bank. After conducting a preliminary survey at Anjani Asrih Waste Bank, there are 20-25% of customers were actively saving. Therefore, a method is needed that can increase customer participation. JUMAMPAH (Waste Monitoring Interpreter) is a method created by researchers who is expected to be able to increase children's knowledge about sorting and saving rubbish so that in the long run it can increase the participants of waste bank customers. The research is quasi-experimental research with a Pre-test design Post-test by using Control Group Design. The location of the study was in Surokarsan 2 Elementary School and Kintelan 1 Elementary School. Surokarsan 2 Elementary School as an experimental group received treatment in the form of counseling using media power points while Kintelan 1 Elementary School as a control group did not receive any treatment. The results of the statistical analysis using Mann-Whitney for knowledge of sorting out the waste, waste saving knowledge obtained p-value 0,000 <0,05 and JUMAMPAH practice indicated there was a significant difference. The conclusionof the research show there is significant difference in the value of the knowledge of sorting out waste, saving waste and JUMAMPAH practices on Surokarsan 2 Elementary School students as an experimental group and Kintelan 1 Elementary School students as a control group.